Maximally improper interference in underlay cognitive radio networks - Lameiro, Christian; Santamaría, I.; Utschick, W.; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Measurement-driven quality assessment of nonlinear systems by exponential replacement - Stein, Manuel; Nossek, Josef A.; Barbé, Kurt (Proc.\ IEEE Int. Instrum. & Meas. Tech.\ Conf.)

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11 n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (Proc. IEEE International Conference on Communications (ICC))

An integrated 118.4 to122 GHz low noise phase-locked loop (PLL) in 0.13 µm SiGe BiCMOS technology - Ali, U.; Bober, M.; Thiede, Andreas (2016 German Microwave Conference (GeMiC))

Shaped Gaussian Dictionaries for Quantized Networked Control Systems with Correlated Dropouts - Peters, E. G. W.; Quevedo, D. E.; stergaard, J. (Trans. Signal Processing)

Maximum Hands-Off Control: A Paradigm of Control Effort Minimization - Nagahara, M.; Quevedo, D. E.; Nešić, D. (Trans. Automat. Contr.)

Multiple Descriptions for Packetized Predictive Control - stergaard, J.; Quevedo, D. E. (EURASIP J. Adv. Signal Processing)

Controller and scheduler codesign for feedback control over IEEE 802.15.4 networks - Peters, E. G. W.; Quevedo, D. E.; Fu, M. (Trans. Contr. Syst. Technol.)

Discrete-time hands-off control by sparse optimization - Nagahara, M.; stergaard, J.; Quevedo, D. E. (EURASIP J. Adv. Signal Processing)

Robust stability of a class of Networked Control Systems - Lješnjanin, M.; Nešić, D.; Quevedo, D. E. (Automatica)

Kalman Filtering With Relays Over Wireless Fading Channels - Leong, A. S.; Quevedo, D. E. (Trans. Automat. Contr.)

Characterization of maximum hands-off control - Chatterjee, D.; Nagahara, M.; Quevedo, D. E.; Rao, K. S. M. (Syst. & Contr. Lett.)

On Network Topology Reconfiguration for Remote State Estimation - Leong, A. S.; Quevedo, D. E.; Ahlén, A.; Johansson, K. H. (Trans. Automat. Contr.)

Event Driven Modeling and Characterization of the Second Order Voltage Switched Charge Pump PLL - Ali, Ehsan; Hangmann, Christian; Hedayat, Christian; Haddad, Fayrouz; Rahajandraibe, Wenceslas; Hilleringmann, Ulrich (IEEE Transactions on Circuits and Systems I: Regular Papers)
Keywords: Electrical and Electronic Engineering

Influence of Traps on the Characteristics of ZnO Nanoparticles Thin-Film Transistors - Vidor, Fabio F.; Meyers, Thorsten; Wirth, Gilson I.; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

Self-aligning integration technique for organic electronics - Meyers, Thorsten; Vidor, Fabio F.; Kaijage, Shubi F.; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

Low-voltage DNTT-based thin-film transistors and inverters for flexible electronics - Meyers, Thorsten; Vidor, Fábio F.; Brassat, Katharina; Lindner, Jörg K.N.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Microstructured Metal Layers in Dye Sensitized Solar Cells - Kleine, Andre; Hilleringmann, Ulrich (Micro-Nano-Integration; 6. GMM-Workshop)

ZnO nanoparticle thin-film transistors on flexible substrate using spray-coating technique - Vidor, Fábio F.; Meyers, Thorsten; Wirth, Gilson I.; Hilleringmann, Ulrich (Microelectronic Engineering)
Keywords: Electrical and Electronic Engineering; Surfaces; Coatings and Films; Condensed Matter Physics; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Inverter Circuits Using ZnO Nanoparticle Based Thin-Film Transistors for Flexible Electronic Applications - Vidor, Fábio; Meyers, Thorsten; Hilleringmann, Ulrich (Nanomaterials)
Keywords: General Materials Science; General Chemical Engineering

Organic Field-Effect and Nanoparticle Thin-Film Transistors: Static Model - Romero, Adrian; Gonzalez, Jesus; Hilleringmann, Ulrich; Gloesekoetter, Peter (ANALOG 2016; 15. ITG/GMM-Symposium)

Influence of UV irradiation and humidity on a low-cost ZnO nanoparticle TFT for flexible electronics - Vidor, F. F.; Meyers, T.; Hilleringmann, Ulrich; Wirth, G. I. (2015 IEEE 15th International Conference on Nanotechnology (IEEE-NANO))

Improved rf design using precise 3d near-field measurements and near-field to far-field transformations - Hangmann, C; Mager, T; Khan, S; Hedayat, C; Hilleringmann, Ulrich (Smart System Integration-International Conference and Exhibition on Integration Issues of Miniaturized Systems)

High-Q whispering gallery microdisk resonators based on silicon oxynitride - Hett, T.; Krämmer, S.; Hilleringmann, Ulrich; Kalt, H.; Zrenner, A. (Journal of Luminescence)
Keywords: Condensed Matter Physics; Biochemistry; General Chemistry; Atomic and Molecular Physics; and Optics; Biophysics

Erweiterung des Raman-Nath-Modells zur Analyse von Schlierenabbildungen - Olfert, Sergei; Henning, Bernd (Technisches Messen)

Lehrerbildung im Mechatronik Studium an der Hochschule Hamm-Lippstadt - Jonas-Ahrend, Gabriela; Thikomirov, Dmitri (Digitale Vernetzung der Facharbeit)

Fabrication and characterization of two-dimensional cubic AlN photonic crystal membranes containing zincblende GaN quantum dots - Blumenthal, Sarah; Bürger, Matthias; Hildebrandt, Andre; Förstner, Jens; Weber, Nils; Meier, Cedrik; Reuter, Dirk; As, Donat J. (physica status solidi (c))
We successfully developed a process to fabricate freestanding cubic aluminium nitride (c-AlN) membranes containing cubic gallium nitride (c-GaN) quantum dots (QDs). The samples were grown by plasma assisted molecular beam epitaxy (MBE). To realize the photonic crystal (PhC) membrane we have chosen a triangular array of holes. The array was fabricated by electron beam lithography and several steps of reactive ion etching (RIE) with the help of a hard mask and an undercut of the active layer. The r/a- ratio of 0.35 was deter- mined by numerical simulations to obtain a preferably wide photonic band gap. Micro-photoluminescence (μ-PL) measurements of the photonic crystals, in particular of a H1 and a L3 cavity, and the emission of the QD ensemble were performed to characterize the samples. The PhCs show high quality factors of 4400 for the H1 cavity and about 5000/3000 for two different modes of the L3 cavity, respectively. The energy of the fundamental modes is in good agreement to the numerical simulations.
Keywords: tet_topic_phc; tet_topic_qd

Investigations into Bluetooth Low Energy Localization Precision Limits - Schmalenstroeer, Joerg; Haeb-Umbach, Reinhold (24th European Signal Processing Conference (EUSIPCO 2016))
In this paper we study the influence of directional radio patterns of Bluetooth low energy (BLE) beacons on smartphone localization accuracy and beacon network planning. A two-dimensional model of the power emission characteristic is derived from measurements of the radiation pattern of BLE beacons carried out in an RF chamber. The Cramer-Rao lower bound (CRLB) for position estimation is then derived for this directional power emission model. With this lower bound on the RMS positioning error the coverage of different beacon network configurations can be evaluated. For near-optimal network planing an evolutionary optimization algorithm for finding the best beacon placement is presented.

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (2016 IEEE International Conference on Communications (ICC))

Planar prism spectrometer based on adiabatically connected waveguiding slabs - Civitci, F.; Hammer, Manfred; Hoekstra, H.J.W.M. (Optics Communications)
The device principle of a prism-based on-chip spectrometer for TE polarization is introduced. The spectrometer exploits the modal dispersion in planar waveguides in a layout with slab regions having two different thicknesses of the guiding layer. The set-up uses parabolic mirrors, for the collimation of light of the input waveguide and focusing of the light to the receiver waveguides, which relies on total internal reflection at the interface between two such regions. These regions are connected adiabatically to prevent unwanted mode conversion and loss at the edges of the prism. The structure can be fabricated with two wet etching steps. The paper presents basic theory and a general approach for device optimization. The latter is illustrated with a numerical example assuming SiON technology.
Keywords: tet_topic_waveguide

Full Resonant Transmission of Semiguided Planar Waves Through Slab Waveguide Steps at Oblique Incidence - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Journal of Lightwave Technology)
Sheets of slab waveguides with sharp corners are investigated. By means of rigorous numerical experiments, we look at oblique incidence of semi-guided plane waves. Radiation losses vanish beyond a certain critical angle of incidence. One can thus realize lossless propagation through 90-degree corner configurations, where the remaining guided waves are still subject to pronounced reflection and polarization conversion. A system of two corners can be viewed as a structure akin to a Fabry-Perot-interferometer. By adjusting the distance between the two partial reflectors, here the 90-degree corners, one identifies step-like configurations that transmit the semi-guided plane waves without radiation losses, and virtually without reflections. Simulations of semi-guided beams with in-plane wide Gaussian profiles show that the effect survives in a true 3-D framework.
Keywords: tet_topic_waveguide

Unveiling Nanometer Scale Extinction and Scattering Phenomena through Combined Electron Energy Loss Spectroscopy and Cathodoluminescence Measurements - Losquin, Arthur; Zagonel, Luiz F.; Myroshnychenko, Viktor; Rodríguez-González, Benito; Tencé, Marcel; Scarabelli, Leonardo; Förstner, Jens; Liz-Marzán, Luis M.; García de Abajo, F. Javier; Stéphan, Odile; Kociak, Mathieu (Nano Letters)
Plasmon modes of the exact same individual gold nanoprisms are investigated through combined nanometer-resolved electron energy-loss spectroscopy (EELS) and cathodoluminescence (CL) measurements. We show that CL only probes the radiative modes, in contrast to EELS, which additionally reveals dark modes. The combination of both techniques on the same particles thus provides complementary information and also demonstrates that although the radiative modes give rise to very similar spatial distributions when probed by EELS or CL, their resonant energies appear to be different. We trace this phenomenon back to plasmon dissipation, which affects in different ways the plasmon signatures probed by these techniques. Our experiments are in agreement with electromagnetic numerical simulations and can be further interpreted within the framework of a quasistatic analytical model. We therefore demonstrate that CL and EELS are closely related to optical scattering and extinction, respectively, with the addition of nanometer spatial resolution.
Keywords: tet_topic_plasmonics

How planar optical waves can be made to climb dielectric steps - Hammer, Manfred; Hildebrandt, Andre; Förstner, Jens (Optics Letters)
We show how to optically connect guiding layers at different elevations in a 3-D integrated photonic circuit. Transfer of optical power carried by planar, semi-guided waves is possible without reflections or radiation losses, and over large vertical distances. This functionality is realized through simple step-like folds of high-contrast dielectric slab waveguides, in combination with oblique wave incidence, and fulfilling a resonance condition. Radiation losses vanish, and polarization conversion is suppressed for TE wave incidence beyond certain critical angles. This can be understood by fundamental arguments resting on a version of Snell’s law. The two 90° corners of a step act as identical partial reflectors in a Fabry–Perot-like resonator setup. By selecting the step height, i.e., the distance between the reflectors, one realizes resonant states with full transmission. Rigorous quasi-analytical simulations for typical silicon/silica parameters demonstrate the functioning. Combinations of several step junctions can lead to other types of optical on-chip connects, e.g., U-turn- or bridge-like configurations.
Keywords: tet_topic_waveguide

Subwavelength binary plasmonic solitons - Kou, Yao; Förstner, Jens (Optics Letters)
We study the formation of subwavelength solitons in binary metal-dielectric lattices. We show that the transverse modulation of the lattice constant breaks the fundamental plasmonic band and suppresses the discrete diffraction of surface plasmon waves. New types of plasmonic solitons are found, and their characteristics are analyzed. We also demonstrate the existence of photonic-plasmonic vector solitons and elucidate their propagation properties.
Keywords: tet_topic_polariton

Robust Population Inversion by Polarization Selective Pulsed Excitation - Mantei, D.; Förstner, Jens; Gordon, S.; Leier, Y. A.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Zrenner, Artur (Scientific Reports)
The coherent state preparation and control of single quantum systems is an important prerequisite for the implementation of functional quantum devices. Prominent examples for such systems are semiconductor quantum dots, which exhibit a fine structure split single exciton state and a V-type three level structure, given by a common ground state and two distinguishable and separately excitable transitions. In this work we introduce a novel concept for the preparation of a robust inversion by the sequential excitation in a V-type system via distinguishable paths.
Keywords: tet_topic_qd

Interference of surface plasmons and Smith-Purcell emission probed by angle-resolved cathodoluminescence spectroscopy - Yamamoto, Naoki; Javier García de Abajo, F.; Myroshnychenko, Viktor (Physical Review B)
We investigate the interplay between geometrical lattice resonances and surface plasmons mediating the emission of Smith-Purcell visible light via angle-resolved cathodoluminescence spectroscopy. We observe strong modulations in the dispersion curves of Smith-Purcell radiation (SPR) when they intersect the surface plasmons of silver gratings using a 200-kV transmission electron microscope. The decay of the plasmons away from the grating is directly probed by controlling the electron-beam position relative to the sample surface with nanometer precision. Our measurements are in excellent agreement with numerical simulations, clearly revealing the presence of characteristic Fano profiles resulting from the interference of the light continuum and the discrete plasmon states for each direction of emission. The intensity anomaly in the SPR emission pattern can be well explained from the geometrical consideration of the intersections between the dispersion planes of the SPR and surface plasmon polariton (SPP). A strong and directional SPR beam can be realized under the condition that the SPR dispersion plane comes in contact with the band edge of the SPP dispersion plane.

Detection of ultrasonic plate waves using ceramic strip transducers - Claes, Leander; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Proceedings SENSOR 2015)
Keywords: piezoceramics; strip transducers; plate waveguide; dispersion diagram

Measurement and Analysis of oﬀshore fog occurrences - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 95th AMS Annual Meeting)

Messtechnisches Prinzip eines neuen Einstrahlungsmessgerätes - Bendfeld, Jörg; Balluff, Stefan; Bermpohl, Wolfgang (Wissenschaftliche Verhandlungen 2015 der Deutschen Physikalischen Gesellschaft)

Performance of MERRA Data in Oﬀshore Wind Energy Applications - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Advanced Integration of Oﬀshore Wind Energy into the Grid System by Power to Gas - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Comparison of micro inverters based on practical analysis - Sadati, A.M.; Krauter, Stefan; Bendfeld, Jörg (2015 5th International Youth Conference on Energy (IYCE))

Effective large-scale PV integration: Methods to match load profile with actual PV output - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Assessment of renewable energy resources in cameroon and special regards on energy supply - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Assessment of renewable energy resources and the use of hydro power for fluctuation compensation in Cameroon - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))

Cost, performance, and yield comparison of eight different micro-inverters - Krauter, Stefan; Bendfeld, Jörg (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

BOS cost reduction via direct PV charging of electrical vehicles - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Stabilizing oﬀshore wind farm power feed-in via power to gas storage systems - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Discovering the potential for oﬀshore windfarms trough measurements - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the Karlsruhe Institute of Technology (KIT) - Energy Science Technology 2015)

Wind power forecasting for oﬀshore wind farms - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore wind energy development based on Merra data - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Oﬀshore metocean station for energy purposes - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 10th Conference on Sustainable Development of Energy, Water and Enviroment Systems - SDEWES)

Short term wind and energy prediction for oﬀshore wind farms using neural networks - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (EWEA Forecasting 2015 Technology Workshop)

Integration of Wind Energy in Power System—Modelling of a Market Oriented Energy Concept - Bouyraaman, Yassin; Bendfeld, Jörg; Breymann, Philipp; Krauter, Stefan (Renewable Energy in the Service of Mankind Vol I)

Coupling Mediated Coherent Control of Localized Surface Plasmon Polaritons - Zeuner, Franziska; Muldarisnur, Mulda; Hildebrandt, Andre; Förstner, Jens; Zentgraf, Thomas (Nano Letters)
Keywords: tet_topic_plasmonics

On Optimal Smoothing in Minimum Statistics Based Noise Tracking - Chinaev, Aleksej; Haeb-Umbach, Reinhold (Interspeech 2015)
Noise tracking is an important component of speech enhancement algorithms. Of the many noise trackers proposed, Minimum Statistics (MS) is a particularly popular one due to its simple parameterization and at the same time excellent performance. In this paper we propose to further reduce the number of MS parameters by giving an alternative derivation of an optimal smoothing constant. At the same time the noise tracking performance is improved as is demonstrated by experiments employing speech degraded by various noise types and at different SNR values.
Keywords: speech enhancement; noise tracking; optimal smoothing

Semantic Analysis of Spoken Input using Markov Logic Networks - Despotovic, Vladimir; Walter, Oliver; Haeb-Umbach, Reinhold (INTERSPEECH 2015)
We present a semantic analysis technique for spoken input using Markov Logic Networks (MLNs). MLNs combine graphical models with first-order logic. They areparticularly suitable for providing inference in the presence of inconsistent and incomplete data, which are typical of an automatic speech recognizer's (ASR) output in the presence of degraded speech. The target application is a speech interface to a home automation system to be operated by people with speech impairments, where the ASR output is particularly noisy. In order to cater for dysarthric speech with non-canonical phoneme realizations, acoustic representations of the input speech are learned in an unsupervised fashion. While training data transcripts are not required for the acoustic model training, the MLN training requires supervision, however, at a rather loose and abstract level. Results on two databases, one of them for dysarthric speech, show that MLN-based semantic analysis clearly outperforms baseline approaches employing non-negative matrix factorization, multinomial naive Bayes models, or support vector machines.

DOA-Estimation based on a Complex Watson Kernel Method - Drude, Lukas; Jacob, Florian; Haeb-Umbach, Reinhold (23th European Signal Processing Conference (EUSIPCO 2015))
This contribution presents a Direction of Arrival (DoA) estimation algorithm based on the complex Watson distribution to incorporate both phase and level differences of captured micro- phone array signals. The derived algorithm is reviewed in the context of the Generalized State Coherence Transform (GSCT) on the one hand and a kernel density estimation method on the other hand. A thorough simulative evaluation yields insight into parameter selection and provides details on the performance for both directional and omni-directional microphones. A comparison to the well known Steered Response Power with Phase Transform (SRP-PHAT) algorithm and a state of the art DoA estimator which explicitly accounts for aliasing, shows in particular the advantages of presented algorithm if inter-sensor level differences are indicative of the DoA, as with directional microphones.

BLSTM supported GEV Beamformer Front-End for the 3RD CHiME Challenge - Heymann, Jahn; Drude, Lukas; Chinaev, Aleksej; Haeb-Umbach, Reinhold (Automatic Speech Recognition and Understanding Workshop (ASRU 2015))

Unsupervised adaptation of a denoising autoencoder by Bayesian Feature Enhancement for reverberant asr under mismatch conditions - Heymann, Jahn; Haeb-Umbach, Reinhold; Golik, P.; Schlueter, R. (Acoustics, Speech and Signal Processing (ICASSP), 2015 IEEE International Conference on)
The parametric Bayesian Feature Enhancement (BFE) and a datadriven Denoising Autoencoder (DA) both bring performance gains in severe single-channel speech recognition conditions. The first can be adjusted to different conditions by an appropriate parameter setting, while the latter needs to be trained on conditions similar to the ones expected at decoding time, making it vulnerable to a mismatch between training and test conditions. We use a DNN backend and study reverberant ASR under three types of mismatch conditions: different room reverberation times, different speaker to microphone distances and the difference between artificially reverberated data and the recordings in a reverberant environment. We show that for these mismatch conditions BFE can provide the targets for a DA. This unsupervised adaptation provides a performance gain over the direct use of BFE and even enables to compensate for the mismatch of real and simulated reverberant data.
Keywords: codecs; signal denoising; speech recognition; Bayesian feature enhancement; denoising autoencoder; reverberant ASR; single-channel speech recognition; speaker to microphone distances; unsupervised adaptation; Adaptation models; Noise reduction; Reverberation; Speech; Speech recognition; Training; deep neuronal networks; denoising autoencoder; feature enhancement; robust speech recognition

Absolute Geometry Calibration of Distributed Microphone Arrays in an Audio-Visual Sensor Network - Jacob, Florian; Haeb-Umbach, Reinhold (ArXiv e-prints)
Joint audio-visual speaker tracking requires that the locations of microphones and cameras are known and that they are given in a common coordinate system. Sensor self-localization algorithms, however, are usually separately developed for either the acoustic or the visual modality and return their positions in a modality specific coordinate system, often with an unknown rotation, scaling and translation between the two. In this paper we propose two techniques to determine the positions of acoustic sensors in a common coordinate system, based on audio-visual correlates, i.e., events that are localized by both, microphones and cameras separately. The first approach maps the output of an acoustic self-calibration algorithm by estimating rotation, scale and translation to the visual coordinate system, while the second solves a joint system of equations with acoustic and visual directions of arrival as input. The evaluation of the two strategies reveals that joint calibration outperforms the mapping approach and achieves an overall calibration error of 0.20m even in reverberant environments.

Robust Automatic Speech Recognition - Li, Jinyu; Deng, Li; Haeb-Umbach, Reinhold; Gong, Y.

Typicality and Emotion in the Voice of Children with Autism Spectrum Condition: Evidence Across Three Languages - Marchi, Erik; Schuller, Bjoern; Baron-Cohen, Simon; Golan, Ofer; Boelte, Sven; Arora, Prerna; Haeb-Umbach, Reinhold (INTERSPEECH 2015)
Only a few studies exist on automatic emotion analysis of speech from children with Autism Spectrum Conditions (ASC). Out of these, some preliminary studies have recently focused on comparing the relevance of selected prosodic features against large sets of acoustic, spectral, and cepstral features; however, no study so far provided a comparison of performances across different languages. The present contribution aims to fill this white spot in the literature and provide insight by extensive evaluations carried out on three databases of prompted phrases collected in English, Swedish, and Hebrew, inducing nine emotion categories embedded in short-stories. The datasets contain speech of children with ASC and typically developing children under the same conditions. We evaluate automatic diagnosis and recognition of emotions in atypical childrens voice over the nine categories including binary valence/arousal discrimination.

Source Counting in Speech Mixtures by Nonparametric Bayesian Estimation of an infinite Gaussian Mixture Model - Walter, Oliver; Drude, Lukas; Haeb-Umbach, Reinhold (40th International Conference on Acoustics, Speech and Signal Processing (ICASSP 2015))
In this paper we present a source counting algorithm to determine the number of speakers in a speech mixture. In our proposed method, we model the histogram of estimated directions of arrival with a nonparametric Bayesian infinite Gaussian mixture model. As an alternative to classical model selection criteria and to avoid specifying the maximum number of mixture components in advance, a Dirichlet process prior is employed over the mixture components. This allows to automatically determine the optimal number of mixture components that most probably model the observations. We demonstrate by experiments that this model outperforms a parametric approach using a finite Gaussian mixture model with a Dirichlet distribution prior over the mixture weights.

Autonomous Learning of Representations - Walter, Oliver; Haeb-Umbach, Reinhold; Mokbel, Bassam; Paassen, Benjamin; Hammer, Barbara (KI - Kuenstliche Intelligenz)
Besides the core learning algorithm itself, one major question in machine learning is how to best encode given training data such that the learning technology can efficiently learn based thereon and generalize to novel data. While classical approaches often rely on a hand coded data representation, the topic of autonomous representation or feature learning plays a major role in modern learning architectures. The goal of this contribution is to give an overview about different principles of autonomous feature learning, and to exemplify two principles based on two recent examples: autonomous metric learning for sequences, and autonomous learning of a deep representation for spoken language, respectively.
Keywords: Representation learning; Metric learning; Deep representation; Spoken language

Lexicon Discovery for Language Preservation using Unsupervised Word Segmentation with Pitman-Yor Language Models (FGNT-2015-01) - Walter, Oliver; Haeb-Umbach, Reinhold; Strunk, Jan; P. Himmelmann, Nikolaus
In this paper we show that recently developed algorithms for unsupervised word segmentation can be a valuable tool for the documentation of endangered languages. We applied an unsupervised word segmentation algorithm based on a nested Pitman-Yor language model to two austronesian languages, Wooi and Waima'a. The algorithm was then modified and parameterized to cater the needs of linguists for high precision of lexical discovery: We obtained a lexicon precision of of 69.2% and 67.5% for Wooi and Waima'a, respectively, if single-letter words and words found less than three times were discarded. A comparison with an English word segmentation task showed comparable performance, verifying that the assumptions underlying the Pitman-Yor language model, the universality of Zipf's law and the power of n-gram structures, do also hold for languages as exotic as Wooi and Waima'a.

Optimized Selection of Frequencies for Faster-Than-at-Speed Test - Kampmann, Matthias; A. Kochte, Michael; Schneider, Eric; Indlekofer, Thomas; Hellebrand, Sybille; Wunderlich, Hans-Joachim (24th IEEE Asian Test Symposium (ATS'15))

Analyse integral erfasster rotationssymmetrischer Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd

On the optimal configuration of triple-ring-electrodes on piezoceramic transducers towards increased parameter sensitivity of impedance - Kulshreshtha, Kshitij; Jurgelucks, Benjamin; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Analyse integral erfasster Schallwechseldruckverteilungen in Schlierenabbildungen - Olfert, Sergei; Henning, Bernd (XXIX Messtechnisches Symposium)

On the optimal configuration of triple-ring-electrodes on piezoceramic transducers towards increased parameter sensitivity of impedance - Jurgelucks, Benjamin; Kulshreshtha, Kshitij; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten

Model based sensitivity analysis in the determination of viscoelastic material properties using transmission measurements through circular waveguides - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd
Several ultrasonic approaches for material determination are formulated in terms of an (nonlinear) inverse problem, e.g. immersion technique (Castaings et al. (2000)) or plate-waveguide techniques (Marzani et al. (2012)). In this contribution we focus on cylindrical waveguides for ultrasonic material determination and especially on the sensitivity of recorded transmission signals to the material properties. We utilize composite scaled sensitivities to determine the information content that can be achieved by the setup to certain parameters and discuss the limitations of the approach.
Keywords: Sensitivity inverse problem ultrasonic material determination

Transient modeling of ultrasonic guided waves in circular viscoelastic waveguides for inverse material characterization - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd (Measurement Science and Technology)
In this contribution, we present an efficient approach for the transient and time-causal modeling of guided waves in viscoelastic cylindrical waveguides in the context of ultrasonic material characterization. We use the scaled boundary finite element method (SBFEM) for efficient computation of the phase velocity dispersion. Regarding the viscoelastic behavior of the materials under consideration, we propose a decomposition approach that considers the real-valued frequency dependence of the (visco-)elastic moduli and, separately, of their attenuation. The modal expansion approach is utilized to take the transmitting and receiving transducers into account and to propagate the excited waveguide modes through a waveguide of finite length. The effectiveness of the proposed simulation model is shown by comparison with a standard transient FEM simulation as well as simulation results based on the exact solution of the complex-valued viscoelastic guided wave problem. Two material models are discussed, namely the fractional Zener model and the anti-Zener model; we re-interpret the latter in terms of the Rayleigh damping model. Measurements are taken on a polypropylene sample and the proposed transient simulation model is used for inverse material characterization. The extracted material properties may then be used in computer-aided design of ultrasonic systems.
Keywords: viscoelasticity; ultrasonics; guided waves; inverse problem; scaled boundary finite element method

Transient modeling of ultrasonic guided waves in circular viscoelastic waveguides for inverse material characterization - Bause, Fabian; Gravenkamp, Hauke; Rautenberg, Jens; Henning, Bernd (Measurement Science and Technology)

Increasing the sensitivity of electrical impedance to piezoelectric material parameters with non-uniform electrical excitation. - Kulshreshtha, Kshitij; Jurgelucks, Benjamin; Bause, Fabian; Rautenberg, Jens; Unverzagt, Carsten (Journal of Sensors and Sensor Systems)

Schallfeldcharakterisierung mittels Schlierentechnik - Olfert, Sergei; Henning, Bernd

Utilizing guided acoustic waves to measure dispersive material properties of polymers - Rautenberg, Jens; Bause, Fabian; Henning, Bernd (AMA~Conferences 2015)
This contribution will give a short introduction to the most important mechanic and acoustic parameters that are necessary to model and simulate frequency dependent sound propagation (dispersion) in isotropic but linear viscoelastic materials. Furthermore, several experimental techniques to measure these parameters will be discussed, like the dynamic-mechanical analysis and transient ultrasonic techniques. Finally it will be shown how to use the determined material parameters for the simulation of transient signals in a highly attenuative acoustic waveguide.

A High Performance SEU Tolerant Latch - Huang, Zhengfeng; Liang, Huaguo; Hellebrand, Sybille (Journal of Electronic Testing - Theory and Applications (JETTA))

Effiziente Auswahl von Testfrequenzen für den Test kleiner Verzögerungsfehler - Hellebrand, Sybille; Indlekofer, Thomas; Kampmann, Matthias; Kochte, Michael; Liu, Chang; Wunderlich, Hans-Joachim
Keywords: Workshop

Application of Automatic Differentiation for the inverse parameter identification of complex-valued forward models - Webersen, Manuel; Bause, Fabian; Henning, Bernd

Identification of temperature-dependent model parameters of ultrasonic piezo-composite transducers - Webersen, Manuel; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (AMA Conferences 2015)
When performing measurements, the effects of the measurement system itself on the measured data generally must be eliminated. Consequently, those effects, i.e. the system’s dynamic behavior, need to be known. For the piezo-composite transducers in an ultrasonic transmission line, a model based approach is used to describe their dynamic behavior and take into account its dependence on the environment temperature and the acoustic impedance of the target medium. Temperature-dependent model parameters are presented, which are obtained by performing a multiplepart identification process on the transducer model, based on electrical impedance measurements [1]. The identification process uses an inverse approach for optimizing a subset of the model parameters. Additionally, algorithmic differentiation methods are used to determine accurate derivatives. In a final optimization step, impedance measurements taken at different temperatures are used to determine the temperature dependencies of the model parameters. These can then be used to assess the plausibility of the identification results. Additionally, the parameters can be expressed as polynomials in the temperature to take different operating conditions into account.
Keywords: piezo-composite; transducer; temperature dependency; identification; plausibility

Implementation and uncertainty analysis of a test device for electrical impedance measurements using vector network analyzers - Webersen, Manuel; Karzellek, Michael; Bause, Fabian; Henning, Bernd

Towards 100 Gbps Wireless Communication in THz Band with PSSS Modulation: A Promising Hardware in the Loop Experiment - KrishneGowda, Karthik; Messinger, Tobias; Wolf, Andreas; Kraemer, Rolf; Kallfass, Ingmar; Scheytt, Christoph (ICUWB 2015)
Terahertz frequency band of 0.06 - 10 THz is especially interesting for ultra-high-speed wireless communication to achieve data rates of 100 Gbps or higher. To accommodate this demand, advanced terahertz signal processing techniques need to be investigated. Parallel Sequence Spread Spectrum (PSSS) is a physical layer (PHY) baseband technology that seems to be suited for being used for ultra-high speed wireless communication since the receiver architecture is especially simple and can be implemented almost completely in analog hardware. In this paper, a PSSS modulated signal at a chip rate of 20 Gcps with a spectral efficiency of (only) 1 bit/s/Hz is transmitted using a linearity limited 240 GHz wireless frontend. PSSS transceiver models are realized offline in MATLAB/Simulink. The PSSS transmitter generates the PSSS modulated symbols that are loaded onto an Arbitrary Waveform generator (AWG) and then transmitted using the available 240 GHz wireless frontend. A Digital Storage Oscilloscope (DSO) samples and stores the received signal. The PSSS receiver performs synchronization, channel estimation and demodulation. For a coded data rate of 20 Gbps, an eye opening of 40% and a BER of 5.4·10 -5 has been measured. These results are highly promising to achieve data rates of up to 100 Gbps with PSSS modulation using a RF-frontend having higher linear operating range and thus allowing increasing the bandwidth efficiency to 4 b/s/Hz.

Shifting the Analog-Digital Boundary in Signal Processing: Should We Use Mixed-Signal "Approximate" Computing? - Scheytt, Christoph; Javed, Abdul Rehman (Workshop on Approximate Computing)

Analyse von Ausführungszeiten durch Integration einer statischen WCET-Analyse mit einer dynamischen Befehlssatzsimulation am Beispiel der TriCore-Architektur - Adelt, Peer

Miniaturized 122 GHz ISM Band FMCW Radar with Micrometer Accuracy - Scherr, Steffen; Göttel, Benjamin; Ayhan, Serdal; Bhutani, Akanksha; Pauli, Mario; Winkler, Wolfgang; Scheytt, Christoph; Zwick, Thomas (European Microwave Week 2015)
In this paper, a miniaturized 122 GHz ISM band FMCW radar is used to achieve micrometer accuracy. The radar consists of a SiGe single chip radar sensor and LCP off-chip antennas. The antennas are integrated in a QFN package. To increase the gain of the radar, an additional lens is used. A combined frequency and phase evaluation algorithm provides micrometer accuracy. The influence of the lens phase center on the beat frequency phase and hence, the overall accuracy is shown. Furthermore, accuracy limitations of the radar system over larger measurement distances are investigated. Accuracies of 200 μm and 2 μm are achieved over a distance of 1.9 m and 5 mm, respectively.

On the Correlation of HW Faults and SW Errors - Müller, Wolfgang; Wu, Liang; Scheytt, Christoph; Becker, Markus; Schoenberg, Sven (Proceedings of the 1st International Workshop on Resiliency in Embedded Electronic Systems (REES 2014))

Integrated Planar Antenna Designs and Technologies for Millimeter-Wave Applications - Wang, Ruoyu
This thesis investigates the design and realization of integrated planar antennas for millimeter-wave applications. The state-of-the-art antenna integration and packaging technologies are extensively studied, and an antenna design flow is proposed. A number of integrated antenna designs by applying different integration approaches and technologies, i.e. on printed circuit board (PCB), on-chip and in Benzocyclobutene (BCB) above-wafer process, are presented. The designs target not only high performance, but also the practical considerations of low-cost, feasibility, better reliability, and good reproducibility. They cover the industrial, medical, and scientific (ISM) bands of 60 GHz, 122 GHz, and 245 GHz in the millimeter-wave range with outstanding performance in a low-cost fashion by applying innovative, appropriate integration methods and sophisticated design. By applying the localized backside etching (LBE) process the presented on-chip antennas achieve measured peak gains of 6–8.4 dBi for above 100 GHz applications with simulated efficiencies of 54–75%. These figures are comparable to that of on-board or in-package antennas. To the best of my knowledge, the achieved gain of 7.5–8.4 dBi in the band of 124–134 GHz for the 130 GHz on-chip double folded dipole antenna is the highest reported result to date for planar on-chip antennas based on low-resistivity silicon technologies. System demonstrators with integrated antennas are realized and measured. The 60 GHz demonstrator with on-PCB differential bunny-ear antenna and a novel bond-wire compensation scheme achieves a data rate of 3.6 Gbit/s over a 15-meter distance, which was the best reported analog front-end without beamforming function in silicon technology regarding both the data rate and transmission distance at the time of its publication. A 245 GHz single-channel transmitter and a single-channel receiver with integrated on-chip antennas are also demonstrated. An effective isotropic radiated power (EIRP) of 7–8 dBm is achieved for the transmitter, which is the highest reported value at 245 GHz for a SiGe transmitter with a single antenna so far. Furthermore, the receiver has the highest reported integration level for any 245 GHz SiGe receiver. A 245 GHz 4-channel-transmitter array with integrated on-chip antenna array is also realized to achieve spatial power combining, which offers 11 dB higher EIRP than a single-channel transmitter. From the presented results of the thesis it is feasible to realize high performance integrated planar antennas in the entire millimeter-wave range and beyond in a cost-effective fashion.

System Design Considerations for a PSSS transceiver for 100Gbps wireless communication with emphasis on mixed Signal implementation - Javed, Abdul Rehman; Scheytt, Christoph; KrishneGowda, Karthik; Kraemer, Rolf (Wireless and Microwave Technology Conference (WAMICON))
Parallel Sequence Spread Spectrum (PSSS) is a physical layer (PHY) baseband technology which is gaining interest for both wireless and wired multi-gigabit communication systems. PSSS is well suited for mixed signal transceiver implementation including channel equalization and allows for a reduction in power dissipation by avoiding high speed data converters. The architecture of a mixed signal baseband processor for 100 Gbps wireless communication is described that reduces the implementation complexity and results in a consequent reduction in power dissipation and chip area.

System Design and Simulation of a PSSS Based Mixed Signal Transceiver for a 20 Gbps Bandwidth Limited Communication Link - Javed, Abdul Rehman; Scheytt, Christoph (1st URSI Atlantic Radio Science Conference (URSI AT-RASC 2015))
Parallel Sequence Spread Spectrum (PSSS) is a physical layer baseband technology wherein parallel data streams are transmitted simultaneously by spreading them using orthogonal codes. PSSS was selected for the wireless sensor network standard IEEE802.15.4-2006 to increase data rate and improve performance in fading channels for frequency bands below 1 GHz. Since then it has gained interest for both wireless and wired communication links.

Mixed-Signal Baseband Processing for 100 Gbit/s Communications - Scheytt, Christoph; Javed, Abdul Rehman (European Microwave Week 2015)

Mixed-mode Baseband for 100 Gbit/s Wireless Communications - Javed, Abdul Rehman; Scheytt, Christoph; Kraemer, Rolf; Messinger, Tobias; Kallfass, Ingmar

PSSS baseband receiver circuit design - Javed, Abdul Rehman

100 Gigabit pro Sekunde und mehr für das drahtlose Hochgeschwindigkeits-Internet - Scheytt, Christoph; Javed, Abdul Rehman (ForschungsForum Paderborn)

Concept for a hierarchical load control for domestic appliances in smart grids - Stille, Karl Stephan Christian; Böcker, Joachim; Bettentrup, Ralf; Kaiser, Ingo (2014 International Conference on Advances in Green Energy (ICAGE))

Hierarchisches Optimierungskonzept für die Laststeuerung von Haushaltsgeräten - Stille, Karl Stephan Christian; Böcker, Joachim; Bettentrup, Ralf; Kaiser, Ingo (ETG-Fachtagung "Von Smart Grids zu Smart Markets")
Haushaltsgeräte aus der Klasse der "Weißen Ware" tragen mit etwa einem Drittel ($34,2%$ \citeBDEW2013) zum privaten Energieverbrauch bei. Diese Veröffentlichung präsentiert eine Struktur und die dafür notwendige optimale Betriebsstrategie für Weiße Ware in einer Umgebung mit Strompreisen, die wegen der Volatilität der Regenerativen Energien stark fluktuieren. Das vorgeschlagene Konzept nutzt dafür ein dezentrales Energiemanagementsystem, das über drei Hierarchieebenen verteilt ist: die Geräteebene, die Haushaltsebene und die Ortsnetzebene. Auf der Geräteebene nutzt dieses Konzept zusätzlich Betriebsflexibilitäten der Haushaltsgeräte aus.
Keywords: Energy management; hybrid energy storage system; self-optimization; multi-objective optimization; adaptive systems; pareto set; SFB614-D1; SFB614-D2; LEA-Publikation; Eigene

Global Identification of a Low-Order Lumped-Parameter Thermal Network for Permanent Magnet Synchronous Motors - Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Energy Conversion)

An open-loop operation strategy for induction motors considering iron losses and saturation effects in automotive applications - Wallscheid, Oliver; Meyer, Michael; Böcker, Joachim (2015 IEEE 11th International Conference on Power Electronics and Drive Systems)

Design and Identification of a Lumped-Parameter Thermal Network for Permanent Magnet Synchronous Motors Based on Heat Transfer Theory and Particle Swarm Optimisation - Wallscheid, Oliver; Böcker, Joachim (European Conference on Power Electronics and Applications (EPE))

Design and Empirical Identification of a Lumped Parameter Thermal Network for Permanent Magnet Synchronous Motors with Physically Motivated Constraints - Wallscheid, Oliver; Böcker, Joachim (IEEE International Electric Machines and Drives Conference (IEMDC))